2010
DOI: 10.3152/030234210x501199
|View full text |Cite
|
Sign up to set email alerts
|

Brain drain of the scientific community of developing countries: the case of Sri Lanka

Abstract: Many Asian developing countries face an increasing drain of their scientific community as a current challenge. This study identifies the trends in Sri Lanka and investigates the nature and dynamics of the pull and push factors at play here and in host countries. We used the expatriate scientists' database of the National Science Foundation of Sri Lanka and a follow-up survey. A highest proportion of the expatriate scientists are in the USA, followed by Australia. The majority of respondents held postgraduate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…The key reasons that migrants choose to leave their country of origin are recognised as being economic, political, cultural, family, and career factors (Carr, Inkson, & Thorn, 2005). Many studies of migration decision-making have focused on these reasons for the move, usually categorising them as push/pull or macro/micro factors (Anas & Wickremasinghe, 2010;Bushin, 2009;De Jong & Gardner, 1981;Haug, 2008;Kontuly, Smith, & Heaton, 1995;Schoorl et al, 2000). Push and pull factors respectively focus on evaluations of certain characteristics in the source and destination countries (e.g., crime).…”
Section: Reasons For International Movesmentioning
confidence: 99%
“…The key reasons that migrants choose to leave their country of origin are recognised as being economic, political, cultural, family, and career factors (Carr, Inkson, & Thorn, 2005). Many studies of migration decision-making have focused on these reasons for the move, usually categorising them as push/pull or macro/micro factors (Anas & Wickremasinghe, 2010;Bushin, 2009;De Jong & Gardner, 1981;Haug, 2008;Kontuly, Smith, & Heaton, 1995;Schoorl et al, 2000). Push and pull factors respectively focus on evaluations of certain characteristics in the source and destination countries (e.g., crime).…”
Section: Reasons For International Movesmentioning
confidence: 99%
“…A survey conducted by Anas and Wickremasinghe (2010) on Sri Lankan expatriate scientists has identified that higher-quality postgraduate study options available in the OECD as the primary reason for the migration of Sri Lankan scientific community, followed by better career opportunities. In addition, the study reveals that the expatriate scientists are also concerned about push factors such as shortage of intellectual guidance, bureaucratic barriers and low job satisfaction.…”
Section: Reasons For the Migration Of Sri Lankan Professionalsmentioning
confidence: 99%
“…Before academics leave the country, in Sri Lanka, they need to sign an agreement with their university confirming that they will return to their home organization and serve for a particular period back at home university. Sri Lankan expatriates have strong family ties and are sentimental about their country (Anas & Wickremasinghe, 2010). Because of the bond agreement and family attachment, a reasonable number of academics return to their home university.…”
Section: Background Of the Problemmentioning
confidence: 99%